2020
DOI: 10.1515/nanoph-2020-0213
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced two-photon photoluminescence assisted by multi-resonant characteristics of a gold nanocylinder

Abstract: AbstractMulti-resonant plasmonic simple geometries like nanocylinders and nanorods are highly interesting for two-photon photoluminescence and second harmonic generation applications, due to their easy fabrication and reproducibility in comparison with complex multi-resonant systems like dimers or nanoclusters. We demonstrate experimentally that by using a simple gold nanocylinder we can achieve a double resonantly enhanced two-photon photoluminescence of quantum dots, by match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…In particular, these effects have been implemented to improve the photoluminescence (PL) emission from chromophores and quantum emitters [8,9]. Apart from the extensive research on the enhancement of conventional one-photon excited PL, in the last decade, there exists a great interest in studying two-photon excitation PL enhanced by metal NPs [10][11][12][13]. This is an emission Original content from this work may be used under the terms of the Creative Commons Attribution 4.0 licence.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, these effects have been implemented to improve the photoluminescence (PL) emission from chromophores and quantum emitters [8,9]. Apart from the extensive research on the enhancement of conventional one-photon excited PL, in the last decade, there exists a great interest in studying two-photon excitation PL enhanced by metal NPs [10][11][12][13]. This is an emission Original content from this work may be used under the terms of the Creative Commons Attribution 4.0 licence.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the shape and material of the nanoparticle, it may induce either inhibition or enhancement of the relaxation processes and, correspondingly, increase or decrease the lifetime of excited states in these molecules or atoms. The enhancement of the spontaneous emission rate is of great interest for a wide range of applications, particularly in light-emitting devices, single-photon sources, and integrated photonics. Metal nanostructures are widely used in these applications due to the strong enhancement and high confinement of the optical near-fields under incident light illumination in resonance conditions and a consequent significant increase in the radiative decay. , However, emitters near metal nanostructures also experience an increase in the nonradiative decay caused by the high absorption in metals. Therefore, the use of metal nanostructures demands careful control of the relative position of emitters and plasmonic nanoparticles. Recent studies show that the high-index dielectric nanoantennas are a highly promising alternative to metal nanoparticles in controlling the emission decay rates (often referred to as the photon local density of states, LDOS) because of the less-probable nonradiative relaxation channels and a greater variety of the excited modes and their easy control. In particular, dielectric nanoparticles support electric and magnetic resonances (Mie resonances) in the visible and near-infrared spectral range.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, tunable multi-modal plasmonic systems offer the possibility to be coupled to both TPA and emission bands of the fluorophore. To date, several geometries of plasmonic nanoparticles suitable for multi-modal fluorescence enhancement with two-photon excitation have been studied, including nanocylinders [15,16], nanorods [17] and nanosphere assemblies [18]. Two-photon excitation fluorescence of Cy5 dye by dipole and quadrupole modes of gold nanodisks has been studied using numerical simulations [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that fluorescence enhancement factors are higher upon coupling to both TPA and emission bands compared to those with coupled emission only. Recently, gold nanodisks have been used for experimental studies of simultaneous enhancement of excitation and emission of quantum dots [16]. The 10-20-fold higher luminescence brightness is reported in case of two-modal enhanced processes.…”
Section: Introductionmentioning
confidence: 99%